WASP family members and formin proteins coordinate regulation of cell protrusions in carcinoma cells - Sarmiento, Corina (2008)
We examined the role of the actin nucleation promoters neural Wiskott-Aldrich syndrome protein (N-WASP) and WAVE2 in cell protrusion in response to epidermal growth factor (EGF), a key regulator in carcinoma cell invasion. We found that WAVE2 knockdown (KD) suppresses lamellipod formation and increases filopod formation, whereas N-WASP KD has no effect. However, simultaneous KD of both proteins results in the formation of large jagged protrusions with lamellar properties and increased filopod formation. This suggests that another actin nucleation activity is at work in carcinoma cells in response to EGF. A mammalian Diaphanous–related formin, mDia1, localizes at the jagged protrusions in double KD cells. Constitutively active mDia1 recapitulated the phenotype, whereas inhibition of mDia1 blocked the formation of these protrusions. Increased RhoA activity, which stimulates mDia1 nucleation, was observed in the N-WASP/WAVE2 KD cells and was shown to be required for the N-WASP/WAVE2 KD phenotype. These data show that coordinate regulation between the WASP family and mDia proteins controls the balance between lamellar and lamellipodial protrusion activity.